Utilização de geradores de aplicação em processos ágeis de reengenharia - Freitas, Raquel Gonçalves de (Universidade Federal de São Carlos, 2006)
Agile methods, through their principles and values, propose to make software development more flexible, thus satisfying the customer in a rapid and customized way. Quality has a fundamental role both in software development and in software maintenance. It is known that, for a product to have quality, guidelines have to be followed along the whole development process as well as software maintenance. Software reengineering is a solution for those systems in which maintenance grew difficult with time. Some reengineering processes use software patterns which provide success solutions for recurrent problems and, also seek agility, avoiding the waterfall process model. Application generators provide agility in software development, as they help the process automation for a certain domain. This dissertation aims to use application generators, more specifically GawCRe (Gerador de aplicações para web de Clínicas de Reabilitação web application generator for rehabilitation clinics) together with ARA (Arcabouço de Reengenharia Ágil Agile Reengineering Approach), instead of the GREN (Gestão de REcursos de Negócio Business Resource Management) framework. Through a prospective case study, conducted with four legacy systems belonging to the medical clinics domain, it has been observed that ARA supports that applications generators use, although it is necessary to make an adaptation in order to allow it. This is true even though the legacy systems domain is not the same as that of the application generator. The generator adaptation has been easier because it is specified in XML. As the code that it generates is in Java, it has been possible to use the Eclipse environment though to produce the classes diagrams necessary to future maintenance. This enforced the reengineering process adaptation so that the classes diagrams production commended to be prepared before code generation passed to be produced after that generation.
Keywords: Reengenharia de software; Gerador (Programas de computador); Geradores de aplicação; Frameworks; Reuso; XML (Linguagem de marcação de documento); CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO